Clinical and genetic characteristics of Chinese Duchenne/Becker muscular dystrophy patients with small mutations - Gan, Siyi; Liu, Shulei; Yang, Haiyan; Wu, Liwen (Frontiers in Neuroscience, 2022)
Background Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) are amongst the inherited neuromuscular diseases with the highest incidence. Small mutations are less common and therefore have been poorly studied in China. Materials and methods The clinical data of 150 patients diagnosed with DMD/BMD by genetic analysis in Hunan Children’s Hospital from 2009 to 2021 were analyzed. The patients were followed up for an average of 3.42 years and their clinical characteristics were collected. Loss of ambulation (LOA) was used to evaluate the severity of disease progression. The correlation among clinical features, different variants, and glucocorticoid (GC) treatment was analyzed by Cox regression analysis. Results 150 different variants were detected in this study, including 21 (14%) novel mutations, 88 (58.7%) non-sense mutations, 33 (22.0%) frameshift mutations, 22 (14.7%) splicing mutations, and 7 (4.7%) missense mutations. Single-exon skipping and single- or double-exon (double/single-exon) skipping strategies covered more than 90% of patients with small mutations. A case with frameshift mutation combined with Klinefelter’s syndrome (47, XXY) and another one with missense mutation combined with epilepsy was found in our study. De novo mutations accounted for 30.0% of all patients. The mean onset age was 4.19 ± 1.63 years old, and the mean diagnosed age was 5.60 ± 3.13 years old. The mean age of LOA was 10.4 years old (40 cases). 60.7% of them received GC treatment at 7.0 ± 2.7 years old. The main causes of complaints were muscle weakness, high creatine kinase (CK), motor retardation, and family history. The risk factors of LOA were positive family history (HR 5.52, CI 1.26–24.18), short GC treatment duration (HR 0.54, CI 0.36–0.82) and frameshift mutation (HR 14.58, CI 1.74–121.76). DMD patients who treated with GC after 7 years old had a higher risk of earlier LOA compared to those receiving treatment before the age of 7 (HR 0.083, CI 0.009–0.804). Moreover, an earlier onset age, a higher CK value, and a larger LOA population were found in the DMD patients compared to the BMD ones. Finally, the locations of the most frequent mutation were in exon 70 and exon 22. Conclusion In conclusion, 150 small mutations were identified in this study, and 21 of them were discovered for the first time. We found the hotspots of small mutations were in exon 70 and exon 20. Also, the analysis showed that positive family history, frameshift mutation, short duration of GC treatment, and delayed GC treatment resulted in earlier LOA for the DMD patients. Taken together, our findings complement the mutation spectrum of DMD/BMD, benefit us understanding to the DMD disease, and lay foundations for the clinical trials.